Synergistic Effect of Nanophotocatalysis and Nonthermal Plasma on the Removal of Indoor HCHO - Yuanwei Lu; Dinghui Wang; Yuting Wu; Chongfang Ma; Xingjuan Zhang; Chunxin Yang (International Journal of Photoenergy)
Photocatalysis is an effective method of air purification at the condition of a higher pollutant concentration. However, its wide application in indoor air cleaning is limited due to the low level of indoor air contaminants. Immobilizing the nanosized TiO2 particles on the surface of activated carbon filter (TiO2/AC film) could increase the photocatalytic reaction rate as a local high pollutant concentration can be formed on the surface of TiO2 by the adsorption of AC. However, the pollutant removal still decreased quickly with the increase in flow velocity, which results in a decrease in air treatment capacity. In order to improve the air treatment capacity by the photocatalytic oxidation (PCO) method, this paper used formaldehyde (HCHO) as a contaminant to study the effect of combination of PCO with nonthermal plasma technology (NTP) on the removal of HCHO. The experimental results show that HCHO removal is more effective with line-to-plate electrode discharge reactor; the HCHO removal and the reaction rate can be enhanced and the amount of air that needs to be cleaned can be improved. Meanwhile, the results show that there is the synergistic effect on the indoor air purification by the combination of PCO with NTP.